Table of contents, editorial board, and other front matter - James P. Chapman (Journal of Applied Communications, 1975)
Editorial front matter and table of contents for vol. 58, no. 4, Oct.-Dec. (1975) of ACE. ACE is the official Journal of the American Association of Agricultural College Editors.